Rozwiąż równianie.
a)4:x=2:5
b)x/15=4/3
c)3-2x/12=3/2
d)1-x/4=1+x/3
e)2-3x/6=7/3
f)x+4/3=x-2/2
wyznacz liczbę a, mając dany pierwiastek równania.
a)3x-(2x-8)+a=2(x-5), x=0
b)2(2y-3)-4(3y+2)=4-a, y=-1
c)2(z-1)-az=-12-(5+2z), z=1
d)12x+2(x+1)=a(x+2)+14, x=√4
rozwiąż równianie.
a)x(3x-2)-18x²=5x(2-3x)+6
b)x²- 2x(x-1)/3=x(x/3+1)-2
c)x(x-2)/3 - x²-x/2 =x-3/4-x(x/6+1)
d)x(x-1)/4=½x²+2/2

1

Odpowiedzi

2009-12-17T16:09:49+01:00
A)4:x=2:5
2x=20
x=10
b)x:15=4:3
3x=60
x=20
c)3-2x/12=3/2
2(3-2x)=36
6-4x=36
4x=-30
x=-7,5
d)1-x/4=1+x/3
3(1-x)=4(1+x)
3-3x=4+4x
7x=-1
x=-1/7
e)2-3x/6=7/3
3(2-3x)=42
6-9x=42
9x=-36
x=-4
f)x+4/3=x-2/2
2(x+4)=3(x-2)
2x+8=3x-6
x=14
wyznacz liczbę a, mając dany pierwiastek równania.
a)3x-(2x-8)+a=2(x-5), x=0
0-(-8)+a=2(-5)
8+a=-10
a=-18
b)2(2y-3)-4(3y+2)=4-a, y=-1
2(-2-3)-4(-3+2)=4-a
-10+12-8=4-a
a=10
c)2(z-1)-az=-12-(5+2z), z=1
0-a=-12-(5+2)
-a=-19
a=19
d)12x+2(x+1)=a(x+2)+14, x=√4
12√4+2√4+2=a√4+2a+14
14√4+2-14=a√4+2a
14√4-12=a(√4+2)
a=(14√4-12)/(√4+2)(usun niewymiernosc z mianownika)
a=0

rozwiąż równianie.
a)x(3x-2)-18x²=5x(2-3x)+6
3x²-2x-18x²=10x-15x²+6
-12x=6
x=-0,5
b)x²- 2x(x-1)/3=x(x/3+1)-2
x²-2x²+2x/3=1/3x²+x-2 [x3
3x²-6x²+2x=x²+x-2
-4x²+x+2=0
Δ=1+32=33
x1=-1+√33/-8
x2=-1-√33/-8

c)x(x-2)/3 - x²-x/2 =x-3/4-x(x/6+1) [x6


d)x(x-1)/4=½x²+2/2
1 5 1